Synthesis and photoluminescence properties of Pb2+ doped SrAl2B2O7 - (:unkn) unknown (ELSEVIER SCIENCE SA, 2008)
Nanopowders of Pb2+ doped SrAl2B2O7 materials were synthesized by a solution-combustion method using metal nitrates and urea as fuel. The synthesized materials were determined by the powder Xray diffraction. The microstructure of the synthesized materials was investigated using scanning electron microscopy. The photoluminescent properties of Pb2+ doped SrAl2B2O7 materials were studied using spectrofluorometer at room temperature. The emission and excitation peaks of SrAl2B2O7:Pb2+ were observed at 420 and 277 nm, respectively. The Stokes shifts of SrAl2B2O7:Pb2+ were calculated to be 12,292 cm(-1). The dependence of the emission intensity on the Pb2+ concentration for SrAl2B2O7:Pb2+ was investigated. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: inorganic compounds; electron microscopy; powder diffraction; luminescence; BLUE-EMITTING PHOSPHOR; LUMINESCENCE; EU3+